Development of poly(vinyl alcohol)-based membranes by the response surface methodology for environmental applications - Merck, Juliana Zanol; Raota, Camila Suliani; Duarte, Jocelei; Baldasso, Camila; Crespo, Janaina da Silva; Giovanela, Marcelo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The pollution of hydric sources by pharmaceuticals is an issue in many countries, particularly in Brazil. The presence of these substances causes deleterious effects on the environment and human health. One of the main sources of this contamination is domestic sewage, due to the expressive amount of medicines released in their unaltered form. Unfortunately, traditional wastewater treatment is not effective for the removal of pharmaceuticals and, for this reason, membrane technology is an attractive alternative to overcome this issue. In this regard, hydrophilic polymers, such as poly(vinyl alcohol) (PVA), are the most suitable. However, their high affinity with water causes intense swelling, leading to severe modifications in the membrane properties. In view of all these facts, the present work evaluated the swelling of PVA-based membranes, with the aim of finding the membrane preparation method that has the lowest swelling, thereby providing the most suitable characteristics for pharmaceutical removal from wastewater. The membranes were prepared by the casting of a polymeric solution, with PVA as a basis polymer, citric acid as a crosslink agent and glycerol and silver nanoparticles as performance additives. The process optimization was performed using a design of experiments with posterior analysis by the response surface methodology (RSM). The RSM assessed the effect on the membrane swelling of the factors, including citric acid concentration and the time and temperature of crosslinking. The membrane characterization was performed by Fourier-transform infrared (FT-IR) spectroscopy, scanning electron microscopy coupled with a field emission gun (SEM-FEG) and water contact angle (WCA) measurements. Overall, the condition that showed the lowest swelling was obtained with 10% of citric acid and crosslinking for 4 h at 130 °C. Under these conditions, the membrane had a mass swelling of 42% and a dimensional swelling of 24%. Additionally, our statistical analysis revealed that the factors with the dominant effects were the citric acid concentration and the temperature of crosslinking. The FT-IR analysis suggested that the crosslinking occurred by an esterification reaction, as showed by the stretching frequencies of C=O at 1710 cm-1 and ester C-O at 1230 cm-1. Moreover, the SEM-FEG images revealed a smooth and flat surface and a dense cross section with a thickness of ~113 μm. Concerning the WCA, the angle was at ~80°, which is characteristic of hydrophilic materials. Finally, the data suggested that it is possible to optimize the membrane preparation process with adequate properties so that it can be subsequently applied to the removal of pharmaceuticals from hospital wastewater.